Physicochemical Characteristics of Egg White Flour Product of Fermentation of Saccharomyces cereviceae and Sucrose Addition - . Nahariah; E. Abustam; R. Malaka (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2010)
A research was conducted to investigate the influence of fermentation dose of Saccharomyces cereviceae and sucrose addition on maintaining the physical properties of egg white flour. One hundred and thirty five fresh hen eggs were used in the research which were randomly arranged in a factorial experiment of 3 x 3 according to completely randomized design with 3 replications for each treatment combination. The first factor was the level of Saccharomyces cereviceae, i.e. 0%, 0,2% and 0,4% w/w, the second factor was the level of sucrose addition, i.e. 0%, 2 % and 4% w/w. The parameters measured were physical properties (rendemen, water content, pH, reduction sugar and color score). Data analysis indicated that increased level of Saccharomyces cereviceae decreased water content, pH, rendemen, reduction sugar, and color score. Sucrose addition improved yield, sugar reduction, color score, but decreased pH of white egg fluor. Physical chracteristics of egg white flour was similar to those of fresh egg white at all of combination of level Saccharomyces cereviceae and sucrose, but low of reduction sugar content and the best color score was obtained at treatment combination of both high level of Saccharomyces cereviceae and low level of sucrose addition.